2016
DOI: 10.25095/mufad.396702
|View full text |Cite
|
Sign up to set email alerts
|

Finansal Okuryazarlık ve Banka Müşteri Segmentasyonları Üzerine Bir Uygulama

Abstract: Bu çalışma, Tokat merkez ilçede bireysel, ticari ve tarımsal olarak segmente edilebilen banka müşterilerinin finansal okuryazarlık düzeylerini ve hangi segment grubunun daha finansal okuryazar olduğunu ortaya koymaya yöneliktir. Araştırmada, banka segment müşterilerinin finansal okuryazarlık seviyesinin düşük olduğu tespit edilmiştir. Finansal okuryazarlık seviyesinin, söz konusu segment grupları içerisinde en düşük olanının tarımsal segment grubu, en fazla olanının ise ticari segment grubu olduğu bulgularına … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 0 publications
1
3
0
4
Order By: Relevance
“…In the study, a literature review was conducted for measurement tools that can be used to determine the financial literacy levels of 4 th -grade students. As a result of the literature review, it was seen that most of the studies on financial literacy (Akhan & Kılıçoğlu, 2014;Bayram, 2010;Baysa, 2015;Er, Temizel & Sönmez, 2015;Goyal & Kumar, 2021) were done in the high school and above age groups. As Sarıgül (2020) stated in his study, there was no study on the financial literacy of primary school students in domestic thesis studies.…”
Section: Data Collection Tools and Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…In the study, a literature review was conducted for measurement tools that can be used to determine the financial literacy levels of 4 th -grade students. As a result of the literature review, it was seen that most of the studies on financial literacy (Akhan & Kılıçoğlu, 2014;Bayram, 2010;Baysa, 2015;Er, Temizel & Sönmez, 2015;Goyal & Kumar, 2021) were done in the high school and above age groups. As Sarıgül (2020) stated in his study, there was no study on the financial literacy of primary school students in domestic thesis studies.…”
Section: Data Collection Tools and Proceduresmentioning
confidence: 99%
“…It is seen that some of the studies in the literature are scale development or situation determination. When the studies are evaluated, it is revealed that data is mainly collected from secondary schools, high schools, universities, and adults through questionnaires (Akhan & Kılıçoğlu, 2014;Bayram, 2010;Baysa, 2015;Er, Temizel, & Sönmez, 2015;Goyal & Kumar, 2021;Sarıgül, 2020). In this context, it is noteworthy that there are studies conducted on primary school students (Çarıkçı, 2019;Çelikten & Doğan, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Bunlardan 13 tanesi İslami finans okuryazarlığı ve İslami finansal sisteme katılım ile ilgili soruları, yani anketin üçüncü ve dördüncü bölümlerini, tamamen boş bıraktığı için çıkartılarak araştırma 363 öğrenci üzerinden gerçekleştirilmiştir. 5 Anketler, yüz yüze görüşme tekniği kullanılarak grup olarak öğrencilere sınıf ortamında uygulanmıştır. Tablo 1, öğrencilerin demografik bilgilerine ait özet istatistikleri göstermektedir.…”
Section: Araştırmanın öRneklemiunclassified
“…According to the research, emerged that the academic staff were financial literate individuals but they needed more financial education. Baysa and Karaca (2016) made an investigation to present financial literacy levels of bank customers, who could be segmented as retail, corporate and agricultural customers, and which segment group had higher financial literacy levels. The study revealed that, financial literacy of segment customers of banks were found to be at low levels.…”
Section: Literaturementioning
confidence: 99%